A Modified Method Using Static Head-Space Gas Chromatography for Determining the Stability Constants of 1-Alkanol/α-Cyclodextrin Complexation - Misawa, Katsumasa; Hashizaki, Kaname; Taguchi, Hiroyuki; Ogawa, Naotake; Saito, Yoshihiro; Ueda, Haruhisa (Chemical & pharmaceutical bulletin, 2004)
A modification of the conventional static head-space gas chromatography method (SHSGC method) to determine stability constants for 1-alkanol/α-CD inclusion complexes was investigated. The 1 : 1 stability constants determined by this modified SHSGC method are in reasonable agreement with the corresponding values reported previously. The modified SHSGC method precludes the necessity of the calibration curve by the use of Henry's law constant of guest. Consequently, the modified SHSGC method is more advantageous than the conventional SHSGC method because the experimental time required for determination of the stability constant is markedly reduced.